Regresi Data Panel untuk Menguji Pertumbuhan Laba Perusahaan Sub Sektor Makanan Minuman di BEI - Afgita Maharani; Novi Khoiriawati (Owner : Riset dan Jurnal Akuntansi, 2023)
This study examined the effect of Liquidity (Current Ratlo), Solvency (Debt to Asset Ratlo), Activity (Total Asset Turnover), Profitability (Net Proflt Margln), and Investment (Dividend Yield) on Proflt Growth in Sub Sector Companles Food and Beverages llsted on the Indonesla Stock Exchange for the 2018 - 2021 perlod. The research findings suggest that Current Ratlo, DAR, and NPM have a signlficant impact on proflt growth ln the food and beverage lndustry. On the other hand, Total Asset Turnover and Dividend Yield do not have a signiflcant lmpact on proflt growth ln the lndustry. The study employed a panel data regression analysis technique, which ls a statistical method used to examlne the relationshlp between dependent and lndependent variables over time. The research utilized secondary data obtalned from annual flnancial reports of food and beverage companies llsted on the Indonesla Stock Exchange (www.idx.com). The sample for this study was 80 financial report data consisting of the 2018-2021 period, and purposive sampling was used to select the sample. The results of the study suggest that companies in the food and beverage industry can improve their profitability by maintaining high liquidity ratios (Current Ratio) and low debt-to-asset ratios (Debt to Asset Ratio). The findings also suggest that companies can improve their profitability by increasing their net profit margins (NPM). On the other hand, companies do not need to focus on increasing their Total Asset Turnover (TATO) and Dividend Yield (DY) to improve their profit growth ln the food and beverage industry. In conclusion, thls study provides empirical evidence on the factors that influence proflt growth ln the food and beverage lndustry in Indonesia. The findings can be useful for investors, financial analysts, and policymakers who are interested ln the food and beverage industry. Companies ln the industry can use these findings to improve their financial performance and attract more investors.